The Responsibility for the Exceeded Result in the Iraqi Penal Code - Karim Salman Aswad Al-tamimi (Journal of Madenat Alelem University College, 2015)
The basis of penal responsibility in the exceeded crimes is the availability of a causal link between criminal behavior and the result. The responsibility obviates with the obviating of the causal link whenever the criminal result is unpredicted to occur according to the normal course of maters.